SOLIDARITAS SOSIAL DALAM NOVEL TANAH PARA BANDIT KARYA TERE LIYE: ANALISIS WACANA KRITIS - Bintang Ramadhan, Muhammad Dwi; Bintang Ramadhan, M Dwi; Suaedi, Hasan; Afrizal, Mohamad (JURNAL KONFIKS, 2025)
Abstract This study, entitled “Social Solidarity in Tere Liye’s Novel *Tanah Para Bandit: A Critical Discourse Analysis,”focuses on how language is used by Tere Liye to portray forms of social solidarity and power relations among the characters in the novel. The backgrounds of this research is based on the view that literary works do not merely serve as aesthetic media but also as mirrors of social reality rich in values, ideologies, and power relations. Through language, authors construct representations of social realities that reflect the dynamics between traditional and modern societies. To addres these issues, the study employ a qualitative descriptive approach using Émile Durkheim’s theory of social solidarity, which distinguishes between two types of solidarity mechanical and organic alongside Norman Fairclough’s Crittical Discoursse Analys (CDA) model, which encompasses three main dimensions: text (language), discourse practice (power), and social practice (social context). The findings reveal that language in the novel is strategically employed to construct two forms of social solidarity: mechanical solidarity, reflected in shared values, adherence to traditions, and the role of Abu Syik as a moral authority within society; and organic solidarity, manifested through cooperation, division of roles, and social awareness that arise from character interactions. Through deliberate word choices, distinctive speech styles, and powerful narration, Tere Liye presents a picture of social transformation from a traditional society toward a modern one that values collaboration, knowledge, and collective spirit. The novelty of this study lies in the applications of Durkheim’s social solidarity theory within the framework of Fairclough’s Critical Discourse Analysis, aiming to uncover the relationship between language, power, and social reality in modern Indonesian literature. The research gap addressed is the scarcity of studies analyzing forms of social solidarity in Tanah Para Bandit with a focus on deological and power dimensions expressed through language .Keywords: Social Solidarity; Critical Discourse Analysis; Émile Durkheim; Norman Fairclough; Tanah Para Bandit